Building New Understanding Through Experiments: Students' Conceptual Shifts on Projectile Motion - Jamaludin Jamaludin; John Rafafy Batlolona; Ashari Bayu P. Dulhasyim (Universitas Pendidikan Mandalika, 2025)
Students' understanding of the concept of projectile motion is often hindered by misconceptions that are difficult to change through conventional teaching methods. This research explores how direct instruction, which remains relevant and effective in physics education, can be key to fostering conceptual change in students through a qualitative approach involving 39 elementary education teacher students as participants. Data was collected using two main instruments: in-depth interviews and student reflection journals, conducted during active and interactive learning processes. The research findings revealed that direct instruction not only helps students identify and correct misconceptions but also enriches their understanding by connecting the concept of projectile motion to real-life phenomena. Based on the reflection journals, students demonstrated increased awareness of conceptual errors and stated that direct involvement in experimental activities facilitated the internalization of concepts. In-depth interviews also indicated that group discussions, demonstrations, and direct observations of the motion trajectories of objects significantly reinforced their conceptual understanding. This transformation in understanding shows that direct teaching methods can bring abstract physics material to life, turning it into meaningful and applicable learning experiences. The conclusion of the research emphasizes that direct instruction is an effective strategy for improving the quality of students' conceptual understanding, particularly on the topic of projectile motion, and strengthening the foundation for sustainable physics education.